Generating walkability from pedestrians' perspectives using a qualitative GIS method. (October 2019) - Battista, Geoffrey A.; Manaugh, Kevin
Highlights: Current walkability measures poorly account for social factors shaping behavior. We situate the pedestrian as integral to the geographic context of walkability. Pedestrians' testimonies on the move are grounded in space using a qualitative GIS. Findings reveal social and personal factors shaping travel behavior and perceptions. Abstract: Geospatial and audit-based walkability measures have proliferated to evaluate the relationship between the built environment and travel behavior. While these measures robustly predict outcomes like mode choice and physical activity, they poorly account for personal and social factors which mediate our interaction with walkable spaces. User-oriented mobile methods can address these gaps, yet recent studies related to walking in the city seldom ground their data and analysis in space—precluding the extrapolation of users' assessments to comparable locations and missing an opportunity to register the social attributes of physical features. In this methods paper, we advance an analytical framework which grounds pedestrians' sentiments and senses from walking interviews in a qualitative geographic information system (QualGIS) to facilitate the management and analysis of assessment data at their original human scale. We detail its application in a socially and environmentally heterogeneous neighborhood to reveal how organizing social and built spatial relationships in a single geographic information system, and co-analyzing them according to street and pedestrian attributes, can yield insights richer than those from examining physical features alone.